Crisis communication of PT Pertamina Hulu Rokan in the Pollution Case in Rantau Kopar Village - Kasih, Rinai Bening; Lee, Eun-Jin (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2026)
This study analyzes PT Pertamina Hulu Rokan's (PHR) crisis communication strategy in response to allegations of environmental pollution in Rantau Kopar Village in 2025. Using a qualitative, content-analytic approach, the study examined media reports, official statements, and academic literature on environmental communication and Situational Crisis Communication Theory (SCCT). The results of the study show that PT PHR predominantly used a diminishment strategy to reduce perceptions of the crisis's seriousness without admitting fault or apologizing. This strategy was chosen to maintain reputation and reduce legal risk, but it created a gap in public expectations regarding transparency and ecological responsibility. The study recommends strengthening communication strategies through a combination of diminishment, bolstering, and rebuilding elements, and increasing public engagement to sustainably restore public trust.